Parametric integro-interpolation method of solving singular integral equations - Evtushenko, A.A.; Prikarpatsky, A.K. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
Use of a parametric intego-interpolational method is proposed for the study of singular integral equations with a singular kernel of Cauchy type; the method involves replacing the regular part of a quadratic formula with subsequent inversion of a singular integral. Justification is given for the computational scheme employed as well as for an estimate of the rate of convergence of the approximate solution, obtained with its aid, to the exact solution.